Production planning for cloud-based additive manufacturing—A computer vision-based approach - Wang, Yuanbin (2021)
Cloud-based additive manufacturing (AM) has shown its potential in the market in recent years. When the demand increases, it becomes more important to efficiently schedule tasks to achieve lower production time and cost. Current solutions are either less efficient or over-simplified the problem in this situation. Therefore, an intelligent AM production planning system is proposed using computer vision algorithms. It firstly sorts tasks based on their heights, areas and remaining time to deadline. Then, models are projected on the printing plane and an improved vision-based method is applied to efficiently find high quality packing solutions. A comparative study has been conducted to verify the packing result and efficiency. At last, a case study has been displayed to illustrate the usefulness of the proposed method.